Description of a new genus Hispaniococcus from Spain, 31 dicembre 2008 and a new Pseudochermes species from Canary Islands (Hemiptera Coccoidea Eriococcidae Cryptococcidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new genus name Hispaniococcus is described for Ovaticoccus agenjoi (Gomez-Menor, 1954) species on Artemisia sp. from Spain. A new species, Pseudochermes williamsi is described from the Palaearctic Region, on Coffea arabica from Canary Island. The morphological relationship of Borchseniococcus, Calycicoccus, Cryptococcus, Kuwanina, Ovaticoccus, Rhopalotococcus, Pseudochermes and other genera is discussed.
Keywords: scale insects; taxonomy; Eriococcidae; Cryptococcidae; new genus and species; distribution; Canary Islands; Palaearctic Region; generic key